Effect of Some Sudanese Traditional Hot Iron Branding on Cattle Hide Quality - Rehab Eltejani Abdelkarim; Mohammed Alhadi Ebrahiem (Turkish Journal of Agriculture: Food Science and Technology)
This study was designed in order to assess and evaluate the effect of hot iron branding on cattle hide quality. 62 shapes of hot iron branding were detected and classified. Branding damage was evaluated depending on: purpose of application, location in the animal body, branding area, tribe which applied and hide degree. The results showed that, Baggara tribes branding were causing the greater damage on cattle hides; where 71.4% of its brands placed in the abdominal and animal back area (middle of the hide); in proportion to Misseriya Zuraq tribes (68.4%). According to the location of branding, the less tribe that causing damages to the cattle hides were Darfur tribes (14.3%). In terms of branding area Darfur tribes were causing the most branding damages where 42.8% of its brands on cattle hides were between 20-30cm, followed by Baggara tribes where 57.1% of its brands were between 10-20cm then Misseriya Zuraq tribes by 52.6%, and finally North Kordofan tribes of 37.5%. grading of cattle hides depending on the presence of the brand marks the study revealed that, Misseriya Zuraq tribe's brands were obtained the highest percentage (89.4%) of the rejected hides (Scarto= 4 and 5 grades), when compared with North Kordofan tribes (87.5%). For commercial reason brand's were mostly done in the area of 5-10cm but, their effect on cattle hide quality was greater, where 81% of the hides were classified as Scarto.